Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 transfection of guide RNA targeting on MMP9 as anti-cancer therapy in human cutaneous squamous cell carcinoma cell line A431 - Teh, Seoh Wei; Elderdery, Abozer; Rampal, Sanjiv; Subbiah, Suresh Kumar; Mok, Pooi Ling (Termedia Publishing House Ltd., 2023)
Introduction: Cutaneous squamous cell carcinoma (SCC) is the second most common form of skin malignancy, representing around 20% of all skin cancers. It is the main cause of death due to non-melanoma skin cancer every year. Metastatic cutaneous SCC is associated with poor prognosis in patients and warrants a more effective and specific approach such as disruption of genes associated with cancer metastasis. Material and methods: Matrix metalloproteinases (MMPs) are enzymes involved in cancer progression and are regarded as major oncotargets. Among others, MMP9 plays critical roles in tumour progression, angiogenesis, and invasion of cutaneous SCC. We aimed to determine whether the MMP9 gene is a suitable gene target for anti-cancer therapy for cutaneous SCC. We performed clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 transfection of guide RNA (gRNA) targeting the MMP9 gene into human cutaneous SCC cell line A431. Results: Following CRISPR transfection treatment, the viability (p < 0.01) and migratory activities (p < 0.0001) of in vitro cutaneous SCC cells were found to be reduced significantly. The use of quantitative polymerase chain reaction (qPCR) also revealed downregulation of the mRNA expression levels of cancer-promoting genes TGF-β, FGF, PI3K, VEGF-A, and vimentin. Direct inhibition of the MMP9 gene was shown to decrease survivability and metastasis of cutaneous SCC cell line A431. Conclusions: Our findings provided direct evidence that MMP9 is important in the viability, proliferation, and metastasis of cutaneous SCC cells. It serves as a positive foundation for future CRISPR-based targeted anti-cancer therapies in treating skin cancer and other forms of malignancies that involve MMPs as the key determinants. © 2023 Termedia Publishing House Ltd.. All rights reserved.